College Accounting- Intermediate/Advanced (Book). - Griffin, Charles H.; Mobley, Sybil C. (The Accounting Review, 1967)
Reviews the book "College Accounting- Intermediate/Advanced," by Horace Brock, Charles E. Palmer and Fred Archer.